Potentiation of Kras peptide cancer vaccine by avasimibe, a cholesterol modulator - Pan, Jing (EBioMedicine, 2019)
BACKGROUND: No effective approaches to target mutant Kras have yet been developed. Immunoprevention using KRAS-specific antigenic peptides to trigger T cells capable of targeting tumor cells relies heavily on lipid metabolism. To facilitate better TCR/peptide/MHC interactions that result in better cancer preventive efficacy, we combined KVax with avasimibe, a specific ACAT1 inhibitor, tested their anti-cancer efficacy in mouse lung cancer models, where Kras mutation was induced before vaccination. METHODS: Control of tumor growth utilizing a multi-peptide Kras vaccine was tested in combination with avasimibe in a syngeneic lung cancer mouse model and a genetically engineered mouse model (GEMM). Activation of immune responses after administration of Kras vaccine and avasimibe was also assessed by flow cytometry, ELISpot and IHC. FINDINGS: We found that Kras vaccine combined with avasimibe significantly decreased the presence of regulatory T cells in the tumor microenvironment and facilitated CD8+ T cell infiltration in tumor sites. Avasimibe also enhanced the efficacy of Kras vaccines target mutant Kras. Whereas the Kras vaccine significantly increased antigen-specific intracellular IFN-γ and granzyme B levels in CD8+ T cells, avasimibe significantly increased the number of tumor-infiltrating CD8+ T cells. Additionally, modulation of cholesterol metabolism was found to specifically impact in T cells, and not in cancer cells. INTERPRETATION: Avasimibe complements the efficacy of a multi-peptide Kras vaccine in controlling lung cancer development and growth. This treatment regimen represents a novel immunoprevention approach to prevent lung cancer.